Sinosporangium siamense sp. nov., isolated from soil and emended description of the genus Sinosporangium - Chanwit Suriyachadkun; Wipaporn Ngaemthao; Suwanee Chunhametha; Chitti Thawai; Jean-Jacques Sanglier; Vichien Kitpreechavanich (My University, 2014)
An actinomycetes strain A-T 1946(T) that developed spherical sporangia containing non-motile spores on aerial mycelia was isolated from dry deciduous forest soil in Thailand. 16S rRNA gene sequence analysis indicated that strain A-T 1946(T) belongs to the genus Sinosporangium, being closely related to Sinosporangium album 6014(T) (98.8% sequence similarity). The DNA-DNA relatedness values were 43.7-50.9%, which were significantly below 70% and differentiated strain A-T 1946(T) from the closest species. The cell-wall peptidoglycan contained meso-diaminopimelic acid. The whole-cell sugars contained rhamnose, ribose, madurose and glucose. The predominant menaquinone was MK-9(H2). The diagnostic phospholipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylmethylethanolamine, lysophosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol-mannoside, N-acetylglucosamine-containing phospholipids, two unknown phosphoglycolipids and two unknown phospholipids. The predominant cellular fatty acids were unsaturated C(16 : 1) and C(17 : 1), and saturated C(16 : 0) and 10-methyl-C(17 : 0). Following an evaluation of phenotypic, chemotaxonomic and genotypic characteristics, the isolate is proposed to represent a novel species of genus Sinosporangium to be named Sinosporangium siamense sp. nov. The type strain is A-T 1946(T) ( = BCC 29081(T) = NBRC 109515(T)). An emended description of the genus Sinosporangium is also provided.
Keywords: Rhamnose; Diamino acid; Strain (injury); Genomics and Phylogenetic Studies